Research Status and Development Tendency Analysis of Overrunning Clutch - Xiangying Hou; Yuzhe Zhang; Hong Zhang; Jian Zhang; Zhengminqing Li; Rupeng Zhu (Jixie chuandong)
Overrunning clutches，as kernel components to achieve working condition changes，have two different working states of overrunning and engaging. With the development of mechanical transmission system technology，the working condition requirements for overrunning clutch are higher and higher. In order to facilitate further systematic research on overrunning clutch，meet the requirements of new age development of high-end equipment，through combing the related literature of mesh type，friction type two kinds of different types of overrunning clutch，the research hotspot and difficulties of overrunning clutch in recent years are summarized，and the future development direction of the overrunning clutch is analyzed. It is provided a basis and reference for subsequent overrunning clutch research.